Easy-Starter : An Online Crowdfunding Website Using Blockchain - Gupta, Rohan; Gupta, Sandeep Gupta; Gangwar, Leher Gangwar; Gupta, Avani Gupta; Shinde, Vinayak Shinde (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Crowd funding is a method of internet fundraising that started out as a way for the general public to contribute small sums of money to support the initiatives of creative individuals. Crowdfunding allows individuals to invest in start-up businesses by going via a middleman, like a broker-dealer. The present websites have an issue in that they don't offer the Donor Guarantee Policy and they don't have authority over the funds that donors donate. In this paper, we propose to use blockchain technology for crowdfunding. By doing this, we are able to offer a transparent, safe, and safe crowdfunding process. This article aims to facilitate the creation and funding of campaigns by offering interactive forms for campaign designers and funders to easily construct and approve initiatives. The money that was donated to them can be tracked by the donor. Every transaction will be captured by the blockchain and stored as a block. There are costs involved, a chance of failure, and crowd fundraising is not a charity. This is where blockchain technology comes in to offset the possible dangers associated with the traditional fundraising approach. By using a decentralized approach to crowd funding, we can completely eliminate any dangers associated with the traditional crowdfunding model.
Keywords: Crowdfunding; Blockchain; Campaign; Smart Contracts; Request-Approval; Consensus Segmentation; Digital Wallet